AI for Food Quality and Safety: A Model for Monitoring Hygiene and Compliance in Home-Based Food Businesses (International Journal of Food and Nutritional Sciences, 2021)
The rapid rise of home-based food businesses has introduced new opportunities for culinary entrepreneurship while highlighting critical concerns related to food safety and hygiene. This research proposes a novel AI-powered model for ensuring hygiene and regulatory compliance in home-based kitchens without compromising their cultural authenticity and personal appeal. The study engaged 40 home chefs and 230 consumers to co-develop a smart, human-centered model powered by artificial intelligence, computer vision, and predictive analytics. Using techniques such as automated visual hygiene inspection, real-time temperature anomaly detection, and sentiment-based customer feedback analysis, we designed a scalable system that builds trust and compliance. Our results show that AI integration not only enhanced safety but also increased revenue, customer loyalty, and operational efficiency. The model ensures safety without bureaucratic burden, providing a transformative path for local food entrepreneurs. This AI-enhanced model supports sustainable growth in the sector, blending tradition with technology.